PLAYING VICTIM DALAM KEHIDUPAN SOSIAL (ANALISIS PENAFSIRAN IBNU KAṠĪR TERHADAP Q.S AN-NISᾹ’: 112 DALAM TAFSĪR AL-QUR`ᾹN AL-`AẒĪM) - Fitriana Sihaloho; Mardian Idris Harahap; Yuzaidi Yuzaidi (Maktabatun: Jurnal Perpustakaan dan Informasi, 2023)
Every human being has an attitude that can be seen from the positive side and the negative side. One of the negative attitudes that humans have is playing victim. The term playing victim is widely used nowadays to indicate a person who likes to accuse other people of their mistakes, and makes it seem as if he is the victim of that mistake. The actions of the playing victim can be detrimental to the perpetrators, as well as people who are victims of the playing victim treatment. As a result of this act, an innocent person becomes unjustly accused and can damage his good name. The perpetrators of playing victim are found in everyday social life, and can be done by anyone. The purpose of this study is to find out how to understand the playing victim, to know the biography of Ibnu Kaṡīr and Tafsir Al-Qur'an Al-`Aẓīm, and to know the playing victim in Tafsīr Al-Qur`ānAl-`Aẓīm.The type of research used in this research is descriptive qualitative research. This study also used library research and the Al-Qur'an method used in this study, namely the Tahlili (analysis) method.Playing victim is an attitude of someone who accuses and blames other innocent people, and distorts the fact that he is the victim of the mistake even though he himself is the one who did it. In Q.S An-Nisā' verse 112 Ibn Kaṡīr explained that playing victim is an act prohibited by Allah, and this act was once done by Bani Ubairik to Labib bin Sahl and Allah forbade it. This act of playing victim is a sin and will receive a reward from Allah SWT. However, if a human commits the act of playing victim and then realizes his mistake and immediately repents, then Allah will forgive him.